شاہ ولی اللہ کے "تذاکیر ثلاثہ" کے تفسیری اثرات:" تدبرِ قرآن" اور "تبیان القرآن" کا خصوصی مطالعہ: Interpretive Effects of Shāh Walīullāh's "Tazakīr-e-Thalāthah”: A Study of “Tadabbur-e-Quran” and “Tibyān al-Quran” (Al-Qamar, 2019)
“Al-Fawz al-Kabīr fī Usūl al-Tafsīr” by Shāh Walīullāh (1703-1762) has been venerated as a great achievement in the field of the principles of Qur’ānic exegesis. In this book, he has divided the Qur’ānic subjects into five types: ʻIlm al-Mukhāṣamah, ʻIlm al-Aākām, ʻIlm al-Tazkīr bi Aʻlāillāh, ʻIlm al-Tazkīr bi Ayyāmillāh and Ilm al-Tazkīr bil Mawt. These subjects have been used in various ways. Their effects can also be seen in commentaries of the Quran. If the latter three subjects are given the title of "Tazākīr-e-Thalāthah", they become three main subjects instead of five. This article aims to study the effects of "Tazākīr-e-Thalāthah" on exegetical literature, and in this regard, the focus has been on “Tadabbur-e-Quran” and “Tibyān al-Quran”. A closer look at the topics and discussions related to "Tazākīr-e-Thalāthah" in both the commentaries makes it clear that the effects of this division and understanding of "Tazākīr-e-Thalāthah" on both the commentaries are obvious in some matters and in some issues they have adopted their own method or traditional style of exegesis.
Keywords: Al-Fawz al-Kabīr; Shāh Walīullāh; "Tazākīr-e-Thalāthah"; “Tadabbur-e-Quran”; “Tibyān al-Quran”